Family-led rehabilitation in India (ATTEND)—Findings from the process evaluation of a randomized controlled trial. Issue 1 (January 2019) - Liu, Hueiming; Lindley, Richard; Alim, Mohammed; Felix, Cynthia; Gandhi, Dorcas BC; Verma, Shweta J; Tugnawat, Deepak K; Syrigapu, Anuradha; Ramamurthy, Ramaprabhu K; Pandian, Jeyaraj D; Walker, Marion; Forster, Anne; et al.
Background: Training family carers to provide evidence-based rehabilitation to stroke patients could address the recognized deficiency of access to stroke rehabilitation in low-resource settings. However, our randomized controlled trial in India (ATTEND) found that this model of care was not superior to usual care alone. Aims: This process evaluation aimed to better understand trial outcomes through assessing trial implementation and exploring patients', carers', and providers' perspectives. Methods: Our mixed methods study included process, healthcare use data and patient demographics from all sites; observations and semi-structured interviews with participants (22 patients, 22 carers, and 28 health providers) from six sampled sites. Results: Intervention fidelity and adherence to the trial protocol was high across the 14 sites; however, early supported discharge (an intervention component) was not implemented. Within both randomized groups, some form of rehabilitation was widely accessed. ATTEND stroke coordinators provided counseling and perceived that sustaining patients' motivation to continue with rehabilitation in the face of significant emotional and financial stress as a key challenge. The intervention was perceived as an acceptable community-based package with education as an important component in raising the poor awareness of stroke. Many participants viewed family-led rehabilitation as a necessary model of care for poor and rural populations who could not access rehabilitation. Conclusion: Difficulty in sustaining patient and carer motivation for rehabilitation without ongoing support, and greater than anticipated access to routine rehabilitation may explain the lack of benefit in the trial. Nonetheless, family-led rehabilitation was seen as a concept worthy of further development.